2021
DOI: 10.3389/fonc.2021.771454
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Signaling Profiles With Distinct Biological and Clinical Implications in Aggressive CLL Subsets With Stereotyped B-Cell Receptor Immunoglobulin

Abstract: The ontogeny and evolution of chronic lymphocytic leukemia (CLL) are critically dependent on interactions between leukemic cells and their microenvironment, including antigens, the latter recognized through the clonotypic B-cell receptor immunoglobulin (BcR IG). Antigen selection is key to the pathogenesis of CLL, as evidenced by the remarkable skewing of the BcR IG gene repertoire, culminating in BcR IG stereotypy, referring to the existence of subsets of patients with (quasi)identical BcR IG. Notably, certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Each subset displays common genomic abnormalities ( 21 ) as well as highly homogeneous clinical and biological properties ( 22 ). Altogether, the IGHV-D-J gene recombination pattern and the amino acid constitution of the heavy chain variable complementarity determining region 3 (HCDR3) categorize these stereotyped CLL cases into 19 major subgroups ( 1 , 22 , 23 ). Very recently, a detailed study on BCR stereotypy reported that not only 30% but even 41% of all CLL cases can be categorized into stereotypic subgroups with overall 29 major subsets ( 20 ).…”
Section: The Complex Role Of the Bcr Signaling In Cllmentioning
confidence: 99%
“…Each subset displays common genomic abnormalities ( 21 ) as well as highly homogeneous clinical and biological properties ( 22 ). Altogether, the IGHV-D-J gene recombination pattern and the amino acid constitution of the heavy chain variable complementarity determining region 3 (HCDR3) categorize these stereotyped CLL cases into 19 major subgroups ( 1 , 22 , 23 ). Very recently, a detailed study on BCR stereotypy reported that not only 30% but even 41% of all CLL cases can be categorized into stereotypic subgroups with overall 29 major subsets ( 20 ).…”
Section: The Complex Role Of the Bcr Signaling In Cllmentioning
confidence: 99%
“…The antigen-dependent activation is subordinate to the binding of self or exogenous antigens to the BCR, whereas the antigen-independent signaling is initiated by the Ig-Ig interaction within the membrane of the same cell, rather than by activating mutations of the signaling pathway molecules (such as CARD11, CD79a, and CD79b), which appear to be rare [43,44]. Furthermore, ~30% of CLL carries quasi-identical VDJ rearrangement of BCR Ig across different patients, which are groupable in stereotyped subsets, identified by a progressive numbering [45,46]. Remarkably, BCR subset 8, characterized by the IGHV4-39/IGHD6-13/IGHJ5 asset, is frequently associated with peculiar genetic lesions (namely, trisomy 12 and NOTCH1 mutations) linked to aggressive disease and progression of CLL into DLBCL-type RS, which is more common among patients carrying this specific BCR stereotype [7,47,48].…”
Section: Bcr Hyperactivation In Rsmentioning
confidence: 99%
“…In the past 20 years, huge initiatives have been taken to categorize the sequence information of different CLL cases from different parts of the world. With the increasing ease of sequencing and the advent of automated bioinformatic tools to annotate them, it is now possible to classify the CLL cases (one-third of all CLL cases that belongs to stereotyped CLL) into 19 major subsets depending on the IGHV-D-J gene recombination pattern and the length and amino acid composition at the heavy-chain variable complementarity determining region 3 (HCDR3) (reviewed in [2,39,41]). Remarkably, the members of each subset share common disease features such as genetic mutations, chromosomal abnormalities, epigenetic condition, gene expression profiles, defects in certain signal transduction pathways, and most importantly, the clinical prognosis and outcome.…”
Section: Cll Subsetsmentioning
confidence: 99%